A descriptive study on the anti-bacterial effect of oxygenated water on the oral cavity, SY 2004-2005 - Chang, Trinette G.O
Oxygenated water, a new product, which is also sold as drinking water, is fast becoming a popular alternative medicine. Although there are many medical claims and testimonies, the product has no dental therapeutic claims. This descriptive study aimed to assess the bactericidal effect of oxygenated water when used as a mouthwash. The sample population consisted of clerks and interns at UP-PGH. The subjects were asked to rinse using sterile tap water (STW Group), Listerine (L Group), or oxygenated water (OW Group). Afterwards, their oral washings were collected and then determination of population density by pour plate was performed. Specimens underwent tenfold dilution, pour plate, 24-hr incubation and bacterial colony counting. Most of the subjects can brush twice a day, use toothbrush and toothpaste, can visit the dentist at least once a year, and were able to brush even with 24-hr hospital duties. The three groups were similar in most aspects. In spite of these similar aspects, no bacteria were found in the Listerine group while there was bacterial growth for both STW Group and OW Group. There was no significant difference in the bacterial load between the STW Group and OW Group.